Mekanisme Pertahanan Ego Said Mahran Dalam Novel Al-Lisshu Wa Al-Killab Karya Najib Mahfuzh (Kajian Psikologi Sastra Sigmund Freud) - Raudhatul Jannah; Hanisfa Salsabila (‘A Jamiy : Jurnal Bahasa dan Sastra Arab, 2022)
This research is entitled Said Mahran's Self Defense Mechanism in the Novel Al-Lisshu wa Al-Killab by Najib Mahfuzh (Sigmund Freud's Literary Psychology Study). The purpose of this research is to describe the self-defense mechanism used by Said Mahran in dealing with the conflict that befell him. The method used in completing this research is descriptive analysis method using Sigmund Freud's literary psychology approach. The data source of this research is the novel Al-Lisshu Wa Al-Killab by Najib Mahfuzh. The collection technique was carried out by means of observation through reading and recording important data related to the research. The data analysis technique used the Miles and Huberman approach. As for the results of this study, there are five self-defense mechanisms used by Said Mahran, among others: Fantasy, Projection, Diversion, Action Formation and Apathy. The purpose of the self-defense mechanism used by Said Mahran is to reduce anxiety and fear of failure in carrying out and realizing his plans.